The Effect of Wang’s Neck-shoulder Point Technique on Frozen Shoulder Compared to Massage - Wang, Feng (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2019)
Background The traditional exercise technique of traditional Chinese medicine has a good effect on frozen shoulder, but it is more complicated and labor-intensive. The author has discovered a special technique in long-term clinical practice, which has a good effect on the disease and is more simple and practical.Objective To observe the curative effect of Wang’s technique of the Neck shoulder point in treating primary frozen shoulder, and compare it with routine massage.Methodology 80 patients with frozen shoulder were randomly divided into treatment and control groups. The control group was given a routine massage, with the treatment group using Wang’s technique on the Neck shoulder point. Each group received 1 course (10 times) of treatment to observe the curative effect employing a Visual Analog Scale (VAS) and University of California shoulder joint score (UCLA).Results Comparison of clinical efficacy between 2 groups of patients, there was no statistical difference between the 2 groups (p>0.05) on the total effectiveness rate. After the comparison of two groups pre and post treatment, VAS scores were significantly reduced(p<0.05), and the scores of treatment group decreased more significantly than that of the control group(p<0.05), the UCLA scores of both groups were significantly improved after treatment compared with before treatment(p<0.05), There was no significant difference in UCLA score between 2 group(p>0.05).Conclusion The curative effect of new technique is satisfactory and can improve the primary frozen shoulder and the technique can take less time and physical strength, and it also has a greater analgesic effect compared with a routine massage.
Keywords: massage; Acupuncture Points; Bursitis; Medicine; Chinese Traditional; Exercise Therapy; Shoulder Pain